Step down three phase converter / Md Afandi Atan - Atan, Md Afandi (2007)
This paper was conduct to research the step down three phase ac/dc converter involving a simple topology of 6 ideal switches using MATLAB/SIMULINK simulation model. This project consists of two parts. First part is ac-to-dc converter and the second parts are consisting of buck converter. This project considered the total harmonic distortion (THD) which was defined as the power summation ratio of all harmonic components to the fundamental frequency power.